A Bear called Paddington - Bond, Michael; Fortnum, Peggy (Boston : Houghton Mifflin, 2008)
A very small bear found by Mr. and Mrs. Brown at Paddington Station becomes one of the family.
Originally published: Great Britain : Collins, 1958.
Keywords: Bears -- Fiction